No turning back: The history of feminism and the future of women - Freedman, Estelle B. (Ballantine Books, 2002)
Repeatedly declared dead by the media, the women’s movement has never been as vibrant as it is today. Indeed as Stanford professor and award-winning author Estelle B. Freedman argues in her compelling book, feminism has reached a critical momentum from which there is no turning back. Freedman examines the historical forces that have fueled the feminist movement over the past two hundred years–and explores how women today are looking to feminism for new approaches to issues of work, family, sexuality, and creativity. Drawing examples from a variety of countries and cultures, from the past and the present, this inspiring narrative will be required reading for anyone who wishes to understand the role women play in the world. Searching in its analysis and global in its perspective, No Turning Back will stand as a defining text in one of the most important social movements of all time.
Keywords: approches et analyses; cours; discipline; fem1000; histoire; histoire des femmes*; histoire et politique; international; mouvements des femmes*; pratiques féministes; premier cycle; sciences humaines; sexisme; systèmes d'oppressions; thématiques